Stenotrophomonas Maltophilia Endophthalmitis Caused by Surgical Equipment Contamination: an Emerging Nosocomial Infection - Maria A Williams; Ana L Gramajo; Gustavo A Colombres; Juan P Caeiro; Claudio P Juárez; José D Luna (Journal of Ophthalmic & Vision Research, 2014)
Purpose: We report three cases of Stenotrophomonas maltophilia endophthalmitis after uneventful extracapsular cataract extraction with intraocular lens implantation-related to surgical equipment contamination. Case report: All patients developed acute, culture-positive endophthalmitis in a period ranging from 2 to 13 days. Cultures from vitreous tap, as well as those obtained from the hand-piece of the irrigation-aspiration system, revealed S. maltophilia as the causing infectious agent. All patients received intravitreal antibiotic treatment as initial therapy, nevertheless, visual disturbance continued to be present, hence pars plana vitrectomy was required. Conclusion: Contamination of surgical-reusable equipment should be considered in addition to the well-known risk factors associated with development of endophthalmitis by S. maltophilia.